Assessing biomass energy resources in developing countries - Wereko-Brobby, Charles, ed. (Commonwealth Science Council LondonGB, 1986)
Papers discuss different techniques and methodologies for assessing biomass energy resources in developing countries. Contains three case studies on biomass resource assessment in Nigeria, Tanzania and Mauritius. Discusses traditional fuel survey methods, rural energy surveys and systems modelling, inter alia.